MEDICAL ENGINEERING: NEW TECHNOLOGIES IN THE DIAGNOSIS OF CORONARY HEART DISEASE - Kodirova G. I. (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The aim of this project was to study gas analysis methods and the selection of equipment for diagnosing coronary heart disease. Materials and methods: Was examined 80 men aged 30-65 years were divided into the following 3 main groups: I (control) - healthy men aged 30-45 years – 20 people, II - Acute myocardial infarction without a Q wave (NQMI) – 25 people aged 32-60 years, group III – Postinfarction cardiosclerosis (PIC) with stable angina pectoris FC II-IV – 35 persons aged 35-65 years. Results: The highest level of amine in explosives was in group II - 579 + 261 x 10^- 9 g/l, which was 68.24% higher than the control group. Group III had a decrease in amine levels to 17.7 + 2.2 x 1.10^ - 9 g / l compared to group II, and 13.91% more than group I. Therefore, the results of analysis showed that with NQMI the yield of volatile amines in B increased.